Web-Based E-Commerce System Design Using RAD Method: A Case Study of PT Muda Jaya Export - Rizki Setyo Putro Robawa; Nur Cahyo Wibowo; Abdul Rezha Efrat Najaf (Universitas Islam Kuantan Singingi, 2025)
This study focused on the design and development of a web-based e-commerce information system for PT. Muda Jaya Export by employing the Rapid Application Development (RAD) approach. The company had been experiencing inefficiencies in handling transactions, inventory, and order management due to the reliance on manual tools such as Microsoft Excel and communication via WhatsApp. These outdated methods often led to data inconsistencies and delays in processing operations. To address these challenges, the new system was built to streamline and centralize various business functions, including sales transactions, pre-order handling, safety stock monitoring, and reorder point calculation. The platform featured capabilities such as online product ordering, real-time pre-order tracking, automated safety stock and reorder point computations, and secure payment integration through Midtrans. The system was implemented using modern web technologies, including React.js for the frontend, Express.js for the backend, and PostgreSQL for the database. To ensure functionality and user satisfaction, the system underwent testing through the Blackbox Testing technique as well as User Acceptance Testing (UAT). The testing outcomes demonstrated that the newly developed system significantly enhanced the accuracy and efficiency of the company’s sales and inventory operations. With this integrated solution, PT. Muda Jaya Export was better equipped to manage its business processes, reducing operational errors and delays. Furthermore, the system contributed to improved data reliability and provided valuable support for making informed decisions related to inventory levels and customer orders.